A Patient with Eight Intracranial Aneurysms: Endovascular Treatment in Two Sessions - Erol Akgul; Hasan Bilen Onan; Huseyin Tugsan Balli; Nuri Eralp Cetinalp (Case Reports in Neurological Medicine)
The frequency of multiple intracranial aneurysms seen in patients with or without subarachnoid hemorrhage is high. The advancement of the endovascular technique and devices has ensured that endovascular treatment of intracranial aneurysms is the first choice in most cases, especially in unruptured ones. Different combinations of treatment modalities and techniques can be used in the management of multiple aneurysms. But in selected patients without subarachnoid hemorrhage, treatment of all aneurysms in one or more sessions with endovascular techniques is less traumatic than that with surgery. In the literature, the maximum number of aneurysms in one patient treated endovascularly and/or surgically is seven. In this case report, we present, with a review of the literature, a patient with eight intracranial aneurysms, all of which were treated in two sessions with various endovascular techniques. A 40-year-old female patient was admitted due to headache. Angiography showed eight aneurysms in the posterior circulation and, bilaterally, in the anterior circulation. All aneurysms were treated endovascularly in two sessions. In the treatment of the aneurysms, different endovascular techniques were used including flow diverters stents, stent-assisted coiling, Y-stent-assisted coiling, and coiling alone.